DENTIFIKASI POTENSI DAN PENGEMBANGAN UBI KAYU DALAM MENDUKUNG KETAHANAN PANGAN DI WILAYAH KABUPATEN BANJARNEGARA - Sarno Sarno (Sainteks, 2012)
This study aims to research and identification potency of each distric that have the cassava commodity is superior and distribution model of each distric in Banjarnegara regency. The research used is case study and convering 20 distric at Banjarnegara regency FY2008. Data analysis conducted using Location Quotient (LQ), Shift Analysis (SA), Super Impose (SI), Locallization Coefisien, Spesiallization Coefisien. The research result reveals that : (a) The all distric in Banjarnegara regency that have potency to developed cassava that base the harvest and production, (b). The cassava is the superior commodity at Purwonegoro, Bawang, Sigaluh, Punggelan, Karangkobar distric’s and it is not the superior commodity at Susukan, Purworejo Klampok, Mandiraja, Banjarnegara, Madukara, Banjarmangu, Wanadadi, Rakit, Pagentan, Pejawaran, Wanayasa, Kalibening, Pagedongan, and Pandanarum distric’s, (c). The cassava distribution commodity model of each distric in Banjarnegara regency that the cassava is not distribution equally or the location is not everywhere at each distric, except Purwonegoro distric’s is distribution equally, and the all distric’s in Banjarnegara regency are not have speciallitation in activity to developed cassava commodity so the comparative advantage is not same, except Purwonegoro, Bawang, Sigaluh, Punggelan, and Karangkobar distric’s that are have speciallitation in activity to developed cassava commodity so the comparative advantage is same. Keywords : Cassava Commodity, Superior, Distric, Banjarnegara